Cadences and tonal dynamism in Manuel de Sumaya's strict style polyphony (Revista Argentina de Musicología, 2021)
This paper examines the role of cláusulas –polyphonic cadences– in stile antico music composed by Manuel de Sumaya (ca. 1680-1755). This approach is used as a launchpad to a more general analysis of harmonic syntax within the style of the composer. On the basis of observations by scholars who have previously identified bold, 'modernizing' behaviors in Sumaya's harmonic language, the article aims to build an analytical framework that may deepen the knowledge on these features and provide a native understanding of them. In order to do this, a historically informed approach to analysis is adopted. This requires the development of a conceptual and analytical toolbox based on Spanish treatises of this period. Throughout the text, the explanatory force of such theory is tested against the analysis of a selection of works by the composer. In cases where compositional praxis eludes the statements of theory, some alternative strategies are explored, in order to define the most singular features of the style in a historically plausible manner. In this path of enquiry, the analysis of stile antico according to the precepts of basso continuo didactics of the time proves very enlightening.
Keywords: Cadences; stile antico; Historically Informed Analysis; Manuel de Sumaya; Basso continuo